Therapy of tonsillopharyngitis: advantages of an integrated approach. A review - Sergey V. Ryazantsev; Galina S. Maltseva; Svetlana S. Vysockaya (ZAO "Consilium Medicum", 2023)
The problem of pain in the pharynx continues to be the focus of attention of scientists and practitioners for many decades. Despite the emergence of modern methods of diagnosis and treatment, the problem of pharyngoalgia is far from being solved. It has now been established that more than 500 possible etiological factors can be the cause of pharyngoalgia, but the leading place is occupied by inflammatory diseases of the pharynx and palatine tonsils. Taking into account the wide distribution of this nosology among the population and the high risk of complications, especially in childhood, the issues related to the search for effective therapeutic regimens and ways to prevent the development of complications are still relevant. Definitely, the treatment should be safe, comprehensive, justified and individually selected in each case. Adequate therapy started in time allows avoiding the development of adverse effects, reducing the treatment time and improving the patient's quality of life. And for a doctor, it is extremely important to know the differences in the clinical picture of pharyngoalgia caused by different types of microorganisms: bacteria, viruses or fungal flora, since these differences will be decisive in the further tactics of treating the patient. This article is devoted to highlighting the issues of the complex use of the lysine salt of ketoprofen in local and systemic form. The parameters of the analgesic and anti-inflammatory action of the lysine salt of ketoprofen are characterized, and a new scheme for the treatment of inflammatory diseases of the pharynx within a single molecule is proposed. The article also pays attention to the prevention of complications and relapses, and discusses the advantages of the drug pidotimod in immunomodulatory therapy.